Linking rhizosphere bacterial life-history strategies with wheat growth under drought stress - Pan, Yanshuo; Liu, Binhui; Zhuang, Shan; Wang, Hongzhe; Qi, Yanjie; Chen, Jieyin; Lesueur, Didier; Xiao, Liang; Li, Yuzhong; Han, Dongfei (Springer, 2025)
The metabolic complexity of microorganisms can be simplified by classifying them into r-strategists and K-strategists. However, their associations with plant growth during drought remain largely unclear. Herein, we used the ribosomal RNA gene operon (rrn) copy number to characterize bacterial life-history strategies, with increased rrn copy numbers suggesting a shift from K- to r-strategies. We generated a series of bacterial communities with increased rrn copy numbers in rhizosphere. Drought decreased rhizosphere bacterial rrn copy numbers, rather than in root, indicating a prevalence of K-strategies during drought stress in rhizosphere. The rrn copy numbers of rhizosphere communities were negatively related to wheat growth during drought, while no significant associations were observed in control treatment. Rhizosphere bacterial communities with higher rrn copy numbers exhibited less community dissimilarity and tended to be more stable. Moreover, the abundance of most predicted functions decreased with rrn copy numbers in droughtstressed rhizosphere. Co-occurrence network analysis indicated that increased rrn copy numbers in rhizosphere community improved the proportion of negative to positive cohesion, implying more stable networks. Our findings bring up innovative knowledge about the relationships between microbial life-history strategies, communities and plant growth, and highlights the importance of plant-microorganism interactions for plant growth during stress